Geografis Information System Sebagai Media Informasi Persebara Benda – Bendayang Bernilai Budaya Dan Sejarah Di Sumatera Selatan - Muhammad Akbar; Ria Andriyani; Yodi Saputra (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
From the existence of objects - objects of value culture and history, especially the statues in South Sumatra Province is quite a lot in various areas in the South Sumatra. But until now there is no geographic description of the layout of objects - objects that are valuable cultural and historical especially the statues in South Sumatra. The purpose of this study is to establish a web-based geographic information system regarding the distribution of the statues so that users can access information via the Internet and direct berintraksi with the system. The system provides several tools that can be used to berintraksi with map information, zoom in, zoom out. In general, this WebGIS can help the community, and students in search of locations - locations spread of statues in South Sumatra.